Utilization and Benefits of Biogas in The Settlements Along The Siddhartha Highway In Syangja District, Nepal - Gautam, Dilli Raj (The Third Pole: Journal of Geography Education, 2014)
This paper aims at analyzing the benefits of biogas system installed along the Siddhartha Highway in Syangja district. Because of the low level of development, the rural households of Nepal are still utilizing the traditional energy resources. About 87 percent of the total energy requirements in Nepal are met by traditional sources of energy. Among them, 77.3 percent energy has been fulfilled by fuel wood alone. To reduce the household consumption of fuel wood energy and save the environment, time and money, biogas system was introduced in Nepal since 1955. However, 261650 biogas systems are installed in Nepal till now. Among them, 6716 plants are installed in Syangja district, of which 38.56 percent plants are located along the Siddhartha highway. According to the respondents, owing to their social prestige, pollution free indoor environment, easy for cooking, conservation of natural resources and reduced work for women and school children, they are satisfied with their biogas system. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11523 The Third Pole Vol. 11-12, 2012 page:6-11